Two Lesser-Known Mosaic Floors from the 18th-Century Excavations of Villa Arianna at Stabia - Gardelli, Paolo; Ariano, Carmela (Actual Problems of Theory and History of Art, 2019)
The present paper is focused on the study of two lesser-known mosaic floors from rooms 27 and 46 of Villa Arianna at Stabia. The two mosaics were completely removed during the excavations of the 18th century and today are preserved at the National Archaeological Museum of Naples (MANN). The 2010 RAS/Hermitage excavation campaign provided the opportunity to launch a series of investigations that have identified the technique used to detach the two mosaics and transfer them from Castellammare di Stabia to the Royal Palace of Portici, and has recently led to the identification of the mosaics in their present location at the MANN.The first of the two was found inside the room identified in Weber’s plan by the number 34 (no. 27 ofthe current plan), a large rectangular space of about 10,50×5,45 m, most likely an oecus or triclinium, which opened directly onto the square peristyle at the SE of the atrium. Except for the few tesserae, nothing remains of the mosaic in situ, as it was almost completely stripped away during the 18th-century excavations. Four years later, on 15 September 1761, during excavation operations in the atrium (24) of the same villa, the threshold in opus tessellatum was identified inside the vestibule (46) on which the word SALVE was clearly legible. Once detached, the threshold was transported to the Herculanense Museum in the Palazzo Caramanico in Portici where it was assembled with a large mosaic depicting a thiasos with sea monsters and dolphins found during the excavation at the Praedia of Iulia Felix in Pompeii in 1775. The greeting inscription is made with black made with black tesserae on a white monochrome background and is enclosed by a trapezoidal black band.